PREDICTIVE ANALYTICS IN EDUCATION: HOW MACHINE LEARNING IS SHAPING FUTURE CLASSROOMS - Kasran; Kasim Yahijii; Mujahid Damopolii (Al-Hijr: Journal of Adulearn World, 2026)
The integration of predictive analytics in education is transforming the learning environment by enabling personalized learning pathways. Machine learning algorithms, through real-time data analysis, have the potential to forecast student performance, identify at-risk learners, and suggest timely interventions. Traditional educational methods often fail to address the diverse needs of students, and predictive analytics offers a more adaptive approach to teaching and learning. This study explores how machine learning is shaping future classrooms by assessing its impact on student outcomes, engagement, and overall learning experiences. The research aims to determine how AI-driven predictive tools can optimize learning by providing tailored content and real-time feedback. A mixed-methods approach was employed, combining quantitative assessments and qualitative interviews with students and teachers. The results indicate that students who interacted with AI-powered learning tools showed a significant improvement in academic performance and engagement. However, concerns were raised regarding the depersonalization of learning due to the AI’s lack of emotional intelligence. The study concludes that while predictive analytics offers significant benefits in personalizing education, it should complement rather than replace human interaction in the classroom. To fully harness the potential of machine learning, future research should explore the long-term impacts of AI on student development and address ethical concerns related to data privacy.